Напряженное состояние цилиндров слоистой структуры с межфазными дефектами - Верещака, Сергей Михайлович; Жигилий, Д. А. (НТУ "ХПИ", 2006)
On the basis of the discrete-structural theory of the thin shells the variant of the settlement model of multy-layer thin-walled elements from several rigid anisotropic layers is offered. It is considered, that the voltage of cross shift and pressure on the border of contact are equal among themselves. Elastic slipping is admitted on a surface of contact of adjacent layers. The decision of the task is got in vectorially nonlinear production with account of deformations' influence of cross shift and pressure. The status of two-layer transversally isotropic cylindrical shells with interphasal defects of material's structure is investigated. The results of the theoretical researches are compared to experimental data
Keywords: теория оболочек С. П. Тимошенко; вектор; система уравнений равновесия; относительная погрешность; анизотропные цилиндрические оболочки